Enhancing the Adhesion of Hematopoietic Precursor Cell Integrins with Hydrogen Peroxide Increases Recruitment within Murine Gut. Issue 8 (August 2013) - Kavanagh, Dean P. J.; Yemm, Adrian I.; Alexander, J. Steven; Frampton, Jon; Kalia, Neena
Hematopoietic stem cells (HSCs) migrate to injury sites and aid in tissue repair. However, clinical success is poor and is partially due to limited HSC recruitment. We hypothesized that HSC pretreatment with H2 O2 would enhance their recruitment to injured gut. As HSCs are rare cells, the number of primary cells obtained from donors is often inadequate for functional experiments. To circumvent this, in this study we utilized a functionally relevant cell line, HPC-7. Anesthetized mice were subjected to intestinal ischemia-reperfusion (IR) injury, and HPC-7 recruitment was examined intravitally. Adhesion to endothelial cells (ECs), injured gut sections, and ICAM-1/VCAM-1 protein were also quantitated in vitro. H2 O2 pretreatment significantly enhanced HPC-7 recruitment to injured gut in vivo. A concomitant reduction in pulmonary adhesion was also observed. Enhanced adhesion was also observed in all in vitro models. Increased clustering of α4 and β2 integrins, F-actin polymerization, and filopodia formation were observed in pretreated HPC-7s. Importantly, H2 O2 did not reduce HPC-7 viability or proliferative ability. HPC-7 recruitment to injured gut can be modulated by H2 O2 pretreatment. This may be through increasing the affinity or avidity of surface integrins that mediate HPC-7 homing to injured sites or through stimulating the migratory apparatus. Strategies that enhance hematopoietic stem/progenitor cell recruitment may ultimately affect their therapeutic efficacy.